Co-chemotherapy of sambung nyawa (Gynura procumbens (Lour.) Merr.) leaves ethanolic extract and Doxorubicin on breast cancer cell - Edy Meiyanto; Riris Istighfari Jenie (Indonesian Journal of Pharmacy, 2007)
Chemotherapy combination attracted high attention in recent years to cure cancer. This method combines between non-toxic or less toxic phytochemicals and chemotherapeutic agents to sensitize cancer cell, to enhance the efficacy of chemotherapeutic agents as well as to reduce its toxicity to normal tissues. The aim of the present research was to examine whether ethanolic extract of Sambung Nyawa leaves (SNE) or Gynura procumbens (Lour.) Merr. synergizes the therapeutic potential of doxorubicin (Dox) on breast cancer cell line T47D.MTT assay was used to measure the effect of growth inhibitory of the combination therapy on T47D cells. SNE (25-500 μg/mL) treatment of cell resulted in 12-97.% growth inhibition in a dose dependent manner (IC50 90 μg/mL), while Dox (1.8-90 nM) treatment showed inhibitory effect of 16-83.% (IC50 50 nM). The combinations of SNE with Dox (1.8-18 nM) showed synergistic effect (CI<1). These results demonstrate a strong possibility of synergistic efficacy of SNE and Dox combination for breast cancer treatment.Key words: Sambung Nyawa leaves ethanolic extract, doxorubicin, cochemotherapy, T47D human mammary cancer cell.